Energy Poverty: Macroeconomic Insight on Romania, Bulgaria and the Vi?egrad Group within the European Context - Rozalia Kicsi; Aurel Burciu; Ionel Bostan; Raluca Zoltan; Simona Buta (Amfiteatru Economic, 2023)
Recent studies suggest a core-periphery pattern of energy poverty in the European Union. The energy vulnerability of Romania, Bulgaria, and the economies of the Visegrad Group as peripheral countries is frequently attributed to the legacy of the centrally planned economy and post-communist economic transformations towards a market economy. The aim of the paper is to investigate the potential occurrence of a core-periphery pattern and the relative situation of Romania, Bulgaria and the V4 countries in this pattern by employing a model that integrates three energy poverty thresholds, namely physical, technological, and economic. The research findings reveal some disparities among the selected countries following each of these thresholds and suggest the emergence of two clusters that are describable by a core-periphery pattern but, in our opinion, with some different meanings from those stated by classical economic development theory. The evidence provided by our study would prove its value and usefulness, on the one hand, by opening up new research directions and, on the other hand, by describing a state of affairs that calls for increasing attention from macroeconomic decision-makers, all the more so as the contextual factors that have shaped the socioeconomic environment in recent years (the Coronavirus pandemic, the military conflict in Ukraine) add even more value to research in this thematic registry, since not only energy security but also the achievement of sustainable development goals are seriously questioned.
Keywords: Q01; Q43; 330; fuel poverty; vulnerability; disparities; thermal comfort; financial burden